Recent Progress in the Development of a-Se/CMOS Sensors for X-ray Detection - Kaitlin Hellier; Emmie Benard; Christopher C. Scott; Karim S. Karim; Shiva Abbaszadeh (Quantum Beam Science, 2021)
Amorphous selenium (a-Se) is a glass-former capable of deposition at high rates by thermal evaporation over a large area. It was chosen as a direct conversion material due to its appealing properties for imaging in both low and high X-ray energy ranges (<30 keV and <30 keV, respectively). It has a bandgap of 2.2 eV and can achieve high photodetection efficiency at short wavelengths less than 400 nm which makes it appealing for indirect conversion detectors. The integration of a-Se with readout integrated circuits started with thin-film transistors for digital flat panel X-ray detectors. With increasing applications in life science, biomedical imaging, X-ray imaging, high energy physics, and industrial imaging that require high spatial resolution, the integration of a-Se and CMOS is one direct way to improve the high-contrast visualization and high-frequency response. Over the past decade, significant improvements in a-Se/CMOS technologies have been achieved with improvements to modulation transfer function and detective quantum efficiency. We summarize recent advances in integrating and photon-counting detectors based on a-Se coupled with CMOS readout and discuss some of the shortcomings in the detector structure, such as low charge conversion efficiency at low electric field and high dark current at high electric field. Different pixel architectures and their performance will be highlighted.